Gastric Ulcer: An overview (International Journal of Current Research in Physiology and Pharmacology, 2023)
Gastric ulcers are breaks in the mucosa of the stomach lining that penetrate through the muscularis mucosa and extend more than 5 mm in diameter. When alterations occur to the defense mechanisms of the stomach, it can cause changes in the gastric mucosa, eventually resulting in erosion and then ulceration. Non-steroidal anti-inflammatory drugs (NSAIDs) and Helicobacter pylori (H. pylori) infection are the two major factors disrupting mucosal resistance to injury. Gastric ulcers are characterized by discontinuation in the inner lining of the gastrointestinal (GI) tract because of gastric acid secretion or pepsin. It extends into the muscularis propria layer of the gastric epithelium. It usually occurs in the stomach and proximal duodenum. It may involve the lower esophagus, distal duodenum, or jejunum. Epigastric pain usually occurs within 15–30 minutes following a meal in patients with a gastric ulcer. Conversely, the pain with a duodenal ulcer tends to occur 2–3 hours after a meal. The treatments for gastric ulcers, such as proton pump inhibitors (PPIs) and histamine-2 (H2) receptor antagonists, have demonstrated adverse effects, relapses, and various drug interactions. On the other hand, medicinal plants and their chemical compounds are useful in preventing and treating numerous diseases.Keywords: gastric ulcer, NSAIDs, epigastric pain, pathophysiology
Keywords: Gastric ulcer, NSAIDs, Epigastric Pain, Pathophysiology